Barrier Factors Model of Innovation Process in the Furniture Industry Supply Chain (Case Study at PT. Duwa Atmimuda) - Pratiwi, Wiwik; Primadasa, Rangga; Asri, Vikha Indira; Waluyo , Wisnu Budi (Universitas Ahmad Dahlan, 2023)
PT. Duwa Atmimuda is a company engaged in manufacturing in producing stainless metal products and furniture frames. PT. Duwa Atmimuda is experiencing problems with the lack of application of technology in terms of marketing, seen from the absence of social media utilization, causing the company to find it difficult to expand market share. This study aims to identify the factors that hinder the company's innovation process using the Interpretive Structural Modeling (ISM) method and classify the model using MICMAC Analysis. The results showed that the ISM model of the barrier factor for the innovation process in the furniture industry supply chain has 6 levels. After the ISM model is obtained, the next process is to classify each variable indicator on the barrier factors of the innovation process with the help of MICMAC analysis. There are 4 classification clusters, the first cluster (autonomous indicators) has one indicator. While in the second cluster (dependent indicators) there is one indicator. In the third cluster (linkage indicators) there are 9 indicators. In the fourth cluster (independent indicators) there is one indicator. The third cluster (linkage indicators) is the highest cluster of indicator spreads where this indicator has high control and dependence. The conclusion of this study is that there are 12 inhibiting factors in the innovation process which are arranged into six levels of the ISM model and in the MICMAC analysis the third cluster is the highest distribution cluster.